Insulin Withdrawal in Diabetic Kidney Disease: What Are We Waiting for? (2021)
The prevalence of type 2 diabetes mellitus worldwide stands at nearly 9.3% and it is estimated that 20–40% of these patients will develop diabetic kidney disease (DKD). DKD is the leading cause of chronic kidney disease (CKD), and these patients often present high morbidity and mortality rates, particularly in those patients with poorly controlled risk factors. Furthermore, many are overweight or obese, due primarily to insulin compensation resulting from insulin resistance. In the last decade, treatment with sodium–glucose cotransporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP1-RA) have been shown to be beneficial in renal and cardiovascular targets; however, in patients with CKD, the previous guidelines recommended the use of drugs such as repaglinide or dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors), plus insulin therapy. However, new guidelines have paved the way for new treatments, such as SGLT2i or GLP1-RA in patients with CKD. Currently, the new evidence supports the use of GLP1-RA in patients with an estimated glomerular filtration rate (eGFR) of up to 15 mL/min/1.73 m2 and an SGLT2i should be started with an eGFR > 60 mL/min/1.73 m2. Regarding those patients in advanced stages of CKD, the usual approach is to switch to insulin. Thus, the add-on of GLP1-RA and/or SGLT2i to insulin therapy can reduce the dose of insulin, or even allow for its withdrawal, as well as achieve a good glycaemic control with no weight gain and reduced risk of hypoglycaemia, with the added advantage of cardiorenal benefits.